Integrating Pharmacology and Gut Microbiota Analysis to Explore the Mechanism of Citri Reticulatae Pericarpium Against Reserpine-Induced Spleen Deficiency in Rats - Yuying Zheng; Xuan Zeng; Pan Chen; Tingting Chen; Wei Peng; Weiwei Su (Frontiers Media S.A., 2020)
Citri Reticulatae Pericarpium (CRP), dried peels of Citrus reticulata Blanco and its cultivars, is an important traditional Chinese medicine for the treatment of spleen deficiency-related diseases. To date, the mechanism of CRP alleviating spleen deficiency has not been well investigated. This study aimed to explore corresponding mechanisms with integrating pharmacology and gut microbiota analysis. Firstly, the therapeutic effects of CRP against spleen deficiency were evaluated in reserpine-treated rats. CRP was found to effectively relieve the typical symptoms of spleen deficiency, including poor digestion and absorption capacity, and disorder in gastrointestinal hormones, immune cytokines and oxidative stress. Secondly, high throughput 16S rRNA gene sequencing revealed that CRP could not only up-regulate some short-chain fatty acids producing and anti-inflammatory bacteria but also down-regulate certain spleen deficiency aggravated related bacteria, eventually led to the rebalance of gut microbiota in spleen deficiency rats. In addition, a total of 49 compounds derived from CRP were identified in rat urine using ultra-high performance liquid chromatography-quadrupole- time of flight tandem mass spectrometry. Network pharmacology analysis showed that apigenin, luteolin, naringenin, hesperidin, hesperetin, homoeriodictyol, dihydroxy-tetramethoxyflavone, and monohydroxy-tetramethoxyflavone were the core bioactive components for CRP against spleen deficiency. Further Gene Ontology analysis and pathway enrichment suggested that therapeutic effects of CRP against spleen deficiency involved multiple pathways such as tumor necrosis factor signaling, hypoxia-inducible factor-1 signaling and Toll-like receptor signaling pathway. These results would help to understand the mechanism of CRP alleviating spleen deficiency and provide a reference for further studies.